Substitution of Carbazole Modified Fluorenes as π-Extension in Ru(II) Complex-Influence on Performance of Dye-Sensitized Solar Cells. (8th August 2011) - Chandrasekharam, Malapaka; Rajkumar, Ganugula; Suresh, Thogoti; Rao, Chikkam Srinivasa; Reddy, Paidi Yella; Yum, Jun-Ho; Nazeeruddin, Mohammad Khaja; Graetzel, Michael
Abstract : A new high molar extinction coefficient ruthenium(II) bipyridyl complex " cis -Ru(4, 4 ′ -bis(9, 9-dibutyl-7-(3, 6-di-tert-butyl-9H-carbazol-9-yl)-9H-fluoren-2-yl)-2, 2 ′ -bipyridine)(2, 2 ′ -bipyridine-4, 4 ′ -dicarboxylic acid)(NCS)2, BPFC " has been synthesized and characterized by FT-IR, 1 H -NMR, and ESI-MASS spectroscopes. The sensitizer showed molar extinction coefficient of18.5 × 10 3  M −1 cm −1, larger as compared to the referenceN 719, which showed14.4 × 10 3  M −1 cm −1 . The test cells fabricated usingBPFC sensitizer employing high performance volatile electrolyte, (E 01) containing 0.05 M I2, 0.1 M LiI, 0.6 M 1, 2-dimethyl-3- n -propylimidazolium iodide, 0.5 M 4- tert -butylpyridine in acetonitrile solvent, exhibited solar-to-electric energy conversion efficiency ( η ) of 4.65% (short-circuit current density (J SC ) = 11.52 mA/cm 2, open-circuit voltage (V OC ) = 566 mV, fill factor = 0.72) under Air Mass 1.5 sunlight, lower as compared to the referenceN 719 sensitized solar cell, fabricated under similar conditions, which exhibited η -value of 6.5% (J SC = 14.3 mA/cm 2, V OC = 640 mV, fill factor = 0.71). UV-Vis measurements conducted on TiO2 films showed decreased film absorption ratios forBPFC as compared to those of referenceN 719. Staining TiO2 electrodes immediately after sonication of dye solutions enhanced film absorption ratios ofBPFC relative to those ofN 719. Time-dependent density functional theory (TD-DFT) calculations show higher oscillation strengths for 4, 4 ′ -bis(9, 9-dibutyl-7-(3, 6-di-tert-butyl-9H-carbazol-9-yl)-9H-fluoren-2-yl)-2, 2 ′ -bipyridine relative to 2, 2 ′ -bipyridine-4, 4 ′ -dicarboxylic acid and increased spectral response for the correspondingBPFC complex.